Determinación del estado refractivo y su incidencia al bajo rendimiento académico en alumnos de 9 a 12 años de la Escuela Dr. Modesto Chávez Franco, Milagro, Guayas, mayo – septiembre 2019 - Bajaña López, Michael Stanley (2019)
Introduction: The determination of refractive status is an essential component in the school age of students. The development of the visual system is carried out from birth to 12 years, low school performance is a problem that occurs at different educational levels. Objective: To determine the refractive state and its impact on the poor academic performance in students from 9 to 12 years old of the Dr. Modesto Chavez Franco School, Milagro, Guayas, May - September 2019. Methodology: Quantitative methodologies and a prospective observational analytical study are used. The type of research to be used was descriptive, cross- sectional, because it describes the types of refractive errors, and the level of academic performance. Results: The decrease in visual acuity is greater in children aged 9 to 10 years with 60%, predominantly male sex with 53%, lens lenses 28%, children between 9 to 10 years (6) have a family history with 25%, the most frequent symptomatology due to blurred vision with 53%, and 62% had low school performance with an average of 6. Conclusion: The majority of children with decreased visual acuity problems, the male sex prevailed, the prevailing refractive error was myopia with 53%, 62% had low school performance, in children aged 9 to 10 years.